The Ages of Man in Fulgentius - Cardigni, Julieta (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2021)
In his Expositio virgilianae continentiae, Fulgentius the Mythographer (5th or 6th century C.E.) makes an exposition and interpretation of the Virgilian Aeneid in an allegorical-etymological key, to which he adds the moral sanction of the Scriptures to close the meaning. The most novel thing about Fulgentius’ work – leaving aside the fact, in itself remarkable, that he is the first Christian commentator of Virgil – is that he transforms the Aeneid into a kind of journey through the stages of human life, making each book of the epic correspond to an age of man. The present work aims to analyze Fulgentius’ operations of interpretation, focusing on the reading the author makes of the Aeneid as an allegory of the life of man. In this frame, we seek to illuminate the exegetical search of Fulgentius, in the conviction that he is not guided by a serious and noble objective, but he intends to mock and ridicule the exegetical techniques that were handled in his time to achieve conciliation and syncretism of Christianity with the pagan literary tradition. In this sense, the author would respond both to the menippean mold that is perceived in his work and to the broader context of Late Antiquity, in which reflection and concern for the discourse and its possibilities of construction of meaning are the order of the day.